Potassium Fertilization Alters the Morphogenetic, Structural, and Productive Characteristics of Panicum maximum Cultivars - Emmanuel Lievio de Lima Véras; Gelson dos Santos Difante; Alexandre Romeiro de Araújo; Denise Baptaglin Montagner; Gabriela Oliveira de Aquino Monteiro; Carolina Marques Costa Araújo; Antonio Leandro Chaves Gurgel; Manuel Cláudio Motta Macedo; Jéssica Gomes Rodrigues; Juliana Caroline Santos Santana (Grasses)
The objective was to evaluate the effects of potassium fertilization on the morphogenetic, structural, and productive characteristics of Panicum maximum (cvs. Tanzania, Quênia, Mombaça, Zuri, Massai, and Tamani). The design was in randomized blocks with four doses of potassium (K) 0, 205, 410, and 820 mg dm−3, divided into 5 applications. The analyzed variables were leaf appearance rate (LAR), leaf elongation rate (LER), stem elongation rate (SER), leaf senescence rate (LSR), leaf life span (LLS), phyllochron (PC), number of live leaves (NLL), final leaf length (FLL), tiller population density (TPD), and forage mass (FM). LAR increased by 0.00216 leaves tiller on day-1 (p = 0.0354) and LER increased by 0.00980 cm tiller on day-1 for each milligram of K (p = 0.0402). There was an increase in FLL of 0.16, 0.08, and 0.07 days for the cultivars Mombaça, Massai, and Tamani, respectively, for each milligram of K applied (p = 0.0034). The TPD of the cultivar Tamani increased linearly by 0.074 tillers/pot for each milligram of K (p = 0.0226), and the cultivar Massai showed a quadratic behavior. The TPD of the other cultivars was not influenced by the increase in the K doses. For forage mass (FM), the cultivars Mombaça and Quênia increased by 0.16 and 0.39 g DM/pot for each milligram of K added to the soil. The cultivars Tanzânia, Zuri, Massai, and Tamani showed maximum point at doses of 261.35, 279.45, 300.57, and 275.86 mg dm−3 K, respectively. Potassium fertilization linearly increased leaf appearance and elongation, with maximum productivity reached at a K dose of 430 mg dm−3, except for the cultivars Mombaça and Quênia, which responded up to a K dose of 820 mg dm−3.